PREGNANCY MIDWIFE CARE WITH A FOCUS ON PERINEAL MASSAGE INTERVENTION TO PREVENT PERINEAL LACERATIONS - Marcella Cristi Ananda; Sri Untari; Nurul Kodiyah (Lppm Unan, 2023)
Background; Perineal lacerations can occur due to spontaneous tears or episiotomy. While the perineal wound itself will have its own impact on the mother, namely discomfort and bleeding disorders, while spontaneous perineal lacerations occur due to tension in the vaginal area during childbirth, can also occur due to the psychological burden of facing the birth process. Method; The research design that the researchers used was a case study research design. The population in this study were third trimester pregnant women with gestational age >34 weeks. The sample in this study amounted to 1 respondent. Results; After being given a perineal massage intervention which was carried out 2-3 x/week with a time of 5-10 minutes during labor, Mrs. R experienced grade I perineal lacerations. Conclusion; Perineal massage in pregnant women can prevent perineal lacerations during labour. This perineal massage can be applied in private midwife practice or performed by the patient himself at home regardless of parity.